DESIGN AND DEVELOPMENT OF PLANTAIN FIBRE EXTRACTION MACHINE (Nigerian Journal of Technology, 2018)
The traditional retting technique of extracting plantain fibres is faced with various constraints such as longer extraction time and poor fibre production rate. This study is targeted at overcoming the limitations associated with traditional methods of extracting plantain fibres through the development of electrically powered machine capable of extracting plantain fibres. The method employed involves the selection of appropriate materials, design, fabrication and assembly of the various components of the machine parts. From the analysis a 2 horsepower electric motor is required to drive the machine. The length of flat-belt required to drive the pulley was  at an angle of lap on the smaller pulley of 2.87 rad. A resultant load of   act on 11.6 mm diameter shaft with maximum bending moment of 10.33 Nm. The total weight of shaft, pulping drum and bearing on frame was 67.51 N. Also, a force of 150 N, 200 N and 250 N could pulp a thickness of plantain ribs of approximately, 6 mm, 6.5 mm and 7 mm, respectively. The test result showed that the machine could extract a sliced pseudo stem thickness between 4.0 mm and 10 mm at 27 and 42 seconds, respectively. It is expected that the plantain fibre extraction machine fabricated would save plantain fibre production time. http://dx.doi.org/10.4314/njt.v37i2.14